Development and validation of the geriatrics health behavior questionnaire (GHBQ) - Maryam Bakhshandeh Bavarsad; Mahshid Foroughan; Nasibeh Zanjari; Gholamreza Ghaedamini Harouni; Zahra Jorjoran Shushtari (BMC, 2022)
Abstract Background Considering the importance of health behaviors in health outcomes, it is necessary to assess health behaviors precisely. This study aimed to develop and validate The Geriatrics Health Behavior Questionnaire among Iranian older adults. Methods This cross-sectional and methodological study was conducted on 420 community older adults (age ≥ 60) through random multi-stage sampling. The initial questionnaire has been developed with 22 items and seven subscales based on an extensive literature review, evaluation of related questionnaires, and experts' opinions. Face and content validity were evaluated by interviewing 10 older adults and 18 specialists. The construct validity was evaluated via Known-groups validity and convergent validity. The reliability of the questionnaire was calculated by internal consistency, test-retest, and absolute reliability. Results The face validity was conducted by using interviews with older adults and gathering the specialists' opinions. The items were grammatically and lexically corrected accordingly. Two items were deleted due to CVR < 0.44. Modified Kappa statistic (K*) and I-CVI for all items were higher than 0.88. The average content validity index (S-CVI/Ave) value was 0.94. Three items were deleted to improve the internal consistency; the final GHBQ consisted of 17 items with Cronbach α = 0.72. Acceptable convergent validity was approved by a significant correlation between GHBQ and SF8™ health survey (r = 0.613, P value< 0.001). Independent t-test showed that older adults with education level ≥ high school have significantly higher health behavior scores than those with education level < high school (11.93 ± 2.27 vs. 9.87 ± 2.35, t = − 9.08, p < 0.001). Intra-class correlation coefficient (ICC) for the total questionnaire was 0.92 (95% CI =0.84 to 0.96). Standard Error Measurement (SEM) and Minimal Detectable Change (MDC95) were 0.71 and 1.98, respectively. Conclusion The present study results showed that the Geriatrics Health Behavior Questionnaire had suitable validity and reliability among Iranian older adults. It is recommended to consider its comprehensiveness and yet its briefness in other populations after passing validation.